2D-Coordination polymers based on 1H-indazole-4-carboxylic acid and transition metal ions: magnetic, luminescence and biological properties. Issue 30 (21st July 2020) - García-Valdivia, Antonio A.; Zabala-Lekuona, Andoni; Ramírez-Rodríguez, Gloria B.; Delgado-López, José M.; Fernández, Belén; Cepeda, Javier; Rodríguez-Diéguez, Antonio
Abstract : Five novel multifunctional coordination polymers (CPs) based on 1 H -indazole-4-carboxylic acid are reported. These complexes, the first examples of CPs with this novel ligand, show interesting magnetic, luminescence and biological properties. Abstract : We report the formation of five novel multifunctional coordination polymers based on 1 H -indazole-4-carboxylic acid (HL). To the best of our knowledge, these complexes are the first examples of coordination compounds constructed with this interesting ligand. These materials were synthesized by solvothermal routes, possess different 2D-structures and show interesting magnetic properties due to the copper compound showing an unusual spin-canted effect while the anisotropic cobalt material behaves as a field-induced single molecule magnet. MTT assays performed on human embryonic kidney (HEK293) and mouse skin melanoma (B16-F10) cell lines indicated that the Cd-based compound was the only one exhibiting dose-dependent toxicity on B16-F10 cells, most likely due to the release of toxic Cd(ii ). Cadmium and zinc polymers exhibit interesting luminescence properties. The fact that zinc polymers did not exhibit inherent toxicity against both cancer and non-cancerous cells make this new family an excellent candidate for further investigation in the field of luminescent materials with biomedical applications.